1986
DOI: 10.21273/jashs.111.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Intensity and Carbohydrate Reserves on Flowering in Olive

Abstract: Experiments were designed to alter the carbohydrate status of olive (Olea europaea L.) leaves during the presumed flower induction period. Bearing and nonbearing ‘Oblonga’ olive trees were exposed to either 850 μmol s-1n-2 PAR for 14 hr daily in a 1000 ppm CO2-enriched atmosphere, 150 μmol s-1m-2 PAR for 14 hr daily in 340 ppm CO2, or maintained in a lathhouse at ambient winter conditions of about 350 μmol s-1m-2 PAR and daily temperature fluctuations from 5° to 20°C. The trees exposed to 850 μmol s-1m-2 had 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…54 Source-sink limitation olives also differ in leaf carbohydrate and mineral content. 12,55,56 It follows that carbohydrates play a crucial role in source-sink limitation.…”
Section: Discussionmentioning
confidence: 99%
“…54 Source-sink limitation olives also differ in leaf carbohydrate and mineral content. 12,55,56 It follows that carbohydrates play a crucial role in source-sink limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were conducted to determine whether changing nutrient concentrations helped to induce Eichhornia crassipes flowering, and the result demonstrated that very low nutrient concentration conditions induced inflorescence formation [7], which reconfirmed the conclusion of Richards [8]. High soluble sugar content promoted S. tonkinensis flowering [9], while it was the opposite for olive [10]. Starch is one of the nutrients that may be converted into soluble sugar to meet the need for metabolic energy during the process of flower bud differentiation [9].…”
Section: Introductionmentioning
confidence: 90%
“…'Manzanilla') reported by Rallo and Martin [16] and Ramos [8]. The differences in the amount of flower formation are expected, considering the well-documented alternate bearing behavior of the olive tree, and could relate to competition for assimilates and different inhibitory factors [22][23][24][25]. It is possible that the consistent temporal patterns we observed between ON and OFF trees, in spite of the quantitative differences in budburst percentages (Figures 1 and 3), support the hypothesis of separate controls of flowering level and dormancy release.…”
Section: The Effect Of Tree Bearing Condition On Reproductive Budburstmentioning
confidence: 99%